2006
DOI: 10.1126/science.1124234
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of the Human Distal Gut Microbiome

Abstract: The human intestinal microbiota is composed of 10 13 to 10 14 microorganisms whose collective genome ("microbiome") contains at least 100 times as many genes as our own genome. We analyzed ~78 million base pairs of unique DNA sequence and 2062 polymerase chain reactionamplified 16S ribosomal DNA sequences obtained from the fecal DNAs of two healthy adults. Using metabolic function analyses of identified genes, we compared our human genome with the average content of previously sequenced microbial genomes. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

53
2,907
5
61

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 4,021 publications
(3,104 citation statements)
references
References 32 publications
53
2,907
5
61
Order By: Relevance
“…1 , 2 The ‘gut-brain axis‘ had already been studied before this field of research gained new momentum a decade ago with the characterization of the gut microbiome. 3 Although the underlying molecular mechanisms remain elusive, the gut microbiota has been shown to modulate behavior and brain processes, including pain perception, 2 stress responsiveness, 4 prefrontal myelination, 5 and brain biochemistry. 1 Experimental manipulation of the gut microbial community composition was shown to be able to modify the host's neural function.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 The ‘gut-brain axis‘ had already been studied before this field of research gained new momentum a decade ago with the characterization of the gut microbiome. 3 Although the underlying molecular mechanisms remain elusive, the gut microbiota has been shown to modulate behavior and brain processes, including pain perception, 2 stress responsiveness, 4 prefrontal myelination, 5 and brain biochemistry. 1 Experimental manipulation of the gut microbial community composition was shown to be able to modify the host's neural function.…”
Section: Introductionmentioning
confidence: 99%
“…It contains approximately 10 13 –10 14 bacteria that colonize environmentally exposed surfaces 3, 4. Colonization begins in earnest after birth, with the mother normally providing the bacterial inoculum that seeds the microbiota of her offspring 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the bacterial communities of each surface have a similar taxonomic composition, but through the course of infancy each surface develops a microbiota with a unique composition that stabilizes during adulthood 2, 6, 7. In the adult gastrointestinal tract, the microbiota is dominated by bacteria from two phyla: the Bacteroidetes and Firmicutes 3. There are representatives from other bacterial phyla, including Proteobacteria and Acintobacteria, but they form only a minor fraction of the bacterial taxa present 1, 3.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of microbes residing in the human body, especially in the gut, outnumbers that of human cells [3]. A vast array of recent studies has identified many microbial enterotypes in the human gut [4], [5], [6], [7], [8], [9], [10] and their potential roles in immunity [5], [7], [8], development [8], digestion [9], and other functions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the studies have used 16S rRNA gene sequencing to understand the community structure, composition, and functional diversity of the human gut microbiome [1], [2], [3], [4]. The success of these culture-independent studies depends primarily on the quality and quantity of metagenomic DNA isolated from the given samples [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%